ANALISIS QSAR SENYAWA TURUNAN MEISOINDIGO SEBAGAI ANTIKANKER PAYUDARA - Ananto, Agus Dwi (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2019)
Quantitative Structure and Relationship (QSAR) of meisoindigo derivative compounds was successfully carried out. The purpose of this study was to find out the best model of meisoindigo derivative compounds as breast anticancer. The research method of this research using the semiempirical PM3 method. The semiempirical method of PM3 was chosen as a better method because it has model results that more represent physicochemical aspects. The selection of the best mathematical model is done by multilinear regression statistical analysis of the calculation data obtained. The results of this study formulate model 5 as the best model with a formula Log 1/IC50 = 44.316 + (-0.0000282*Eis.at) + (-0.257*Âµ) + (-0.054*LogP) + (0.014*EH) + (-7.241*qC6) + (-1.734*qC9) + (25.711*qO10) + (7.309*qN11) + (94.825*qC13) + (58.794*qO14) + (5.866*qC15)